STUDI KOMPARATIF PENGARUH NITROCARBURIZING TERHADAP SIFAT MEKANIK DAN SIFAT FISIK BAJA KARBON RENDAH - Saputro, Yunus Bayu; Nurhadi; R. Faiz Listyanda (POLITALA PRESS, 2024)
The increasingly widespread use of structural steel in everyday life, despite its tendency to undergo corrosion, results in financial losses and poses safety risks if damage occurs. This study aims to analyze the effects of nitrocarburizing on the hardness, corrosion rate, microstructure, and composition of low-carbon materials SS400 and ASTM A36. The research method used is experimental. Data analysis techniques were obtained by comparing the results of each test. The nitrocarburizing test results showed differences in hardness values and corrosion rates for SS400 and ASTM A36. The SS400 test results at 350°C were 221.04 VHN and 0.26993 mpy, at 400°C were 278.85 VHN and 0.30959 mpy, and at 450°C were 440.39 VHN and 1.4548 mpy. The ASTM A36 test results at 350°C were 377.43 VHN and 0.43071 mpy, at 400°C were 399.58 VHN and 0.085371 mpy, and at 450°C were 230.83 VHN and 1.4336 mpy.